(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1864)
This article documents four stone circles in Aberdeenshire. The author notes their placement, how many stones are still standing and the type of stone used. The centre of each circle was excavated and although these excavations found evidence of human remains, the author could not conclude whether that meant these stone circles were the site of human sacrifice or burial monuments.